Mathematical Simulations and On-Road Experimentations of the Vibration Energy Harvesting from Mining Dump Truck Hydro-Pneumatic Suspension - Wenguang Wu; Sha Zhang; Zhiyong Zhang (Shock and Vibration)
Running on an unpaved road, the truck’s vibration is weakened by the HPS (hydro-pneumatic suspension) and transformed into thermal energy which was finally dissipated in the air. This paper is aimed to discuss the energy harvesting potential from the truck HPS on random road excitation. In this manner, a quarter-truck model was built and the kinetic energy method that can be used to calculate the power of the dissipated energy was proposed. The dissipated instantaneous power (The peak value is 180 kW) and average power (12 kW) were analyzed which showed 15-fold of difference. The different road class analysis results showed that the E-class road excited 4-fold of power than that of D-class road. The influence of damping and stiffness on the dissipation power was analyzed. The results showed that the power excited by the D-class road is less sensitive than the E-class road. Furthermore, it is interesting that the results also show that the value of average dissipated power when running on E-class road is very close to the speed value, respectively. The real road test of the truck was carried out in an open pit mine and verified the simulation results. The final results demonstrated that the vibrational energy that harvested from the HPS could reduce oil consumption by about 4% in theory.